Blood supply of the human carotid body - Atieh Seyedian Moghaddam; Stefan H. Geyer; Berna Dogan; Paata Pruidze; Jeremias T. Weninger; Karoline M. Schwendt; Wolfgang J. Weninger (Scientific Reports)
Abstract Glomic arteries (GAs) supply the carotid body (CB), a chemosensory organ at the carotid bifurcation. Accurate knowledge of GA anatomy is essential for CB surgery and understanding the impact of carotid artery atherosclerosis on breathing and blood pressure regulation. This study aims to provide comprehensive, statistically significant data on the number, origin, topology, length, and complexity of human GAs. Employing high-resolution episcopic microscopy (HREM), the Amira® software, and statistics, 120 CBs from 30 female and 30 male body donors were analyzed. CBs were located at the anterior (7.5%), posterior (66.7%), and above the central carotid bifurcation (25.8%). They were supplied by up to five GAs; 25% by a single, and 54% by two GAs. Sixty percent of GAs originated from the external carotid artery. In 85% of CBs receiving multiple GAs, at least one arose from this artery. The average tortuosity value of the GAs was 1.56, and their mean length was 2.36 mm, with male and left-sided GAs being significantly longer. This large-scale, systematic study provides high-resolution 3D data and challenges existing anatomic GA descriptions. It offers a solid foundation for studying carotid artery atherosclerosis’s physiological and pathological implications, and advancing the treatment of CB tumors.